A Content-Based Supplementary Book Development for Islamic Junior High School - Maulana, Muhammmad Irham; Munif; Yulia, Yuyun; Pratiwi, Dwiyani (English Education Department, 2025)
This research focuses on the development of a Content-Based Instruction (CBI)-based supplementary book for English language learning at SMP IICP Puncak Darussalam, an Islamic junior high school. The study addresses the gap in existing educational resources by integrating Islamic values and cultural themes into the English language curriculum. It aims to bridge the disconnect between students' cultural identities and the content they are taught. Using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research involved needs analysis, content design, and expert evaluations to ensure the book’s pedagogical effectiveness and cultural relevance. The supplementary book was developed to align with the school’s vision of preparing students to be proficient in English while reflecting Islamic teachings and values. This study promotes culturally relevant materials to raise student engagement, motivation, and language acquisition. The book is expected to improve the quality of English education in Islamic junior high schools through linguistic skills and cultural awareness.